Promoting participation of agricultural households in the milk market: evidence from northern Cote d’Ivoire - Coulibaly, Jeanne Y.; Balagtas, J.V.; Jabbar, M.A.; Negassa, A. (Norman E. Borlaug Leadership Enhancement in Agriculture Program, 2008)
Increased participation in agricultural markets may alleviate poverty among rural households in Africa. Thus, understanding the determinants of market participation is important for the design and evaluation of development policies. The study described in this brief makes an institutional analysis of dairy markets and evaluates determinants of dairy market participation by agricultural households in Côte d’Ivoire. Results can be used to draw policy recommendations that take into account a larger population of agricultural households. For example, the implications of higher market prices or lower transactions costs can be evaluated for not only the volume of marketed surplus from existing cattle owners, but also for the propensity of rural households more broadly to adopt livestock. The analysis of rural dairy markets in Côte d’Ivoire also represents a rare look at market participation in West Africa. Market participation has been the focus of several economic studies in East Africa, but very few analyses address the issue of participation in dairy markets in West Africa. Thus, this study provides an empirical analysis of the performance of the rural dairy market in Côte d’Ivoire and derives some implications for public policy in the design and evaluation of dairy market development.